Copper-catalyzed three-component reaction to synthesize polysubstituted imidazo[1, 2-a]pyridines. Issue 31 (14th July 2022) - Zhou, Zitong; Luo, Danyang; Li, Guanrong; Yang, Zhongtao; Cui, Liao; Yang, Weiguang
Abstract : Three-component one-pot synthesis of polysubstituted imidazo[1, 2- a ]pyridine derivatives through a base free CuAAC/ring-cleavage process. Abstract : An efficient three-component one-pot and operationally simple cascade of 2-aminopyridines with sulfonyl azides and terminal ynones is reported, providing a variety of polysubstituted imidazo[1, 2- a ]pyridine derivatives in moderate to excellent yields. In particular, the reaction goes a through CuAAC/ring-cleavage process and forms a highly active intermediate α-acyl- N -sulfonyl ketenimine with base free.